Ответ:
Объяснение:
Cu(OH)2 -> CuO + H2O
2Cu + O2 = 2CuO
CuO + 2HNO3 = Cu(NO3)2 + H2O
Cu(NO3)2 + Mg = Mg(NO3)2 + Cu
CuO + H2SO4 = CuSO4 + H2O
CuSO4 + 2NaOH = Cu(OH)2 + Na2SO4
Cu(NO3)2 + 2NaOH = Cu(OH)2 + 2NaNO3
1. Cu(OH)2 = CuO + H2O
2. 2Cu + O2 = 2CuO
3. CuO + 2HNO3 = Cu(NO3)2 + H2O
4. Cu(NO3)2 + Fe = Cu + Fe(NO3)2
5. CuO + H2SO4 = CuSO4 + H2O
6. CuSO4 + 2NaOH = Cu(OH)2 + Na2SO4
7. Cu(NO3)2 + 2NaOH = Cu(OH)2 + 2NaNO3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
Cu(OH)2 -> CuO + H2O
2Cu + O2 = 2CuO
CuO + 2HNO3 = Cu(NO3)2 + H2O
Cu(NO3)2 + Mg = Mg(NO3)2 + Cu
CuO + H2SO4 = CuSO4 + H2O
CuSO4 + 2NaOH = Cu(OH)2 + Na2SO4
Cu(NO3)2 + 2NaOH = Cu(OH)2 + 2NaNO3
1. Cu(OH)2 = CuO + H2O
2. 2Cu + O2 = 2CuO
3. CuO + 2HNO3 = Cu(NO3)2 + H2O
4. Cu(NO3)2 + Fe = Cu + Fe(NO3)2
5. CuO + H2SO4 = CuSO4 + H2O
6. CuSO4 + 2NaOH = Cu(OH)2 + Na2SO4
7. Cu(NO3)2 + 2NaOH = Cu(OH)2 + 2NaNO3